MURDER STRATEGY AND ACHIEVEMENT MOTIVATION UPON STUDENTSâ READING COMPREHENSION - Suparman, Lalu (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2015)
The investigation of this study was the effect of MURDER strategy and achievement motivation toward studentsâreading comprehension at the third graders of Madrasah Aliyah NW Penendem. The design of this study was post-test only control group design. The samples were taken by using the technique of random sampling which involved 80 students. The samples were divided into experimental and control group. The data were collected and administrated using questionnaire and test, which were analyzed using two-ways ANOVA. The results of the study displayed that (1) there is a significant difference on the English reading comprehension between the students who are taught by using MURDER strategy and those who are teught by using conventional strategy (FA=32.3, p 0.05). Keywords:MURDERstrategy, achievement motivation, English reading comprehension ABSTRAK: Penelitian ini meneliti pengaruh strategy MURDER dan motivasi berprestasi terhadap kemampuan pemahaman membaca peserta didik siswa kelas tiga Madrasah Aliyah NW Penendem . Desain penelitian menggunakan rancangan posttest only control group design. Sampel penelitian berjumlah 80 orang peserta didik yang diambil menggunakan teknik random sampling. Pengambilan sampel dibagi kedalam kelompok eksperimen dan kelompok kontrol. Pengumpulan dan pengolahan data diperoleh melalui kuisioner dan tes yang dianalisa menggunakan ANOVA dua jalur. Hasil penelitian mengungkapkan bahwa (1) terdapat perbedaan signifikan kemampuan pemehaman membaca siswa yang mengikuti pembelajaran strategy MURDER dan siswa yang mengikuti pembelajaran konvensional (FA=32,4, p 0,05). Kata kunci: Strategi MURDER, motivasi berprestasi, Kemampuan pemahaman membaca bahasa Inggris.